Association between Apical Periodontitis and Chronic Diseases: An Umbrella Review - Serrão , Gabriella; Pinto , Karem Paula; Alves Ferreira , Cláudio Malizia; Sassone, Luciana Moura; da Silva Fidalgo , Tatiana Kelly; Nogueira Leal Silva , Emmanuel João (Iranian Endodontic Journal, 2023)
Introduction: To assess the methodological quality of systematic reviews (SRs) that evaluated the association between apical periodontitis (AP) and chronic diseases. Materials and Methods: A systematic search was performed in the databases PubMed, Virtual Health Library, Scopus, Cochrane Library, Embase, Web of Science and Open Grey. SRs that evaluated the association between any chronic disease and AP, and that had performed a valid risk of bias assessment were included. The AMSTAR-2 tool was used for quality assessment and each included systematic review received a final categorization as having “high”, “moderate”, “low”, or “critically low” quality. Results: Nine studies that met the eligibility criteria were included. The diseases investigated were cardiovascular diseases, diabetes mellitus, HIV, osteoporosis, chronic liver disease, blood disorders and autoimmune diseases. The systematic reviews included in this umbrella review showed a ‘low’ to ‘high’ quality of evidence. Conclusion: There are substantial heterogeneity and several methodological concerns in the included studies. It was observed a positive association between diabetes mellitus and apical periodontitis with limited evidence, no association between HIV and apical periodontitis and a positive association between apical periodontitis and cardiovascular disease, blood disorders, chronic liver disease, osteoporosis and autoimmune diseases with moderate evidence.